Syndromic gingival fibromatosis associated with pathogenic variation in the voltage-gated potassium channel gene KCNH1: a case report and proposed treatment protocol - Nhat Minh Do; Pierre Klienkoff; Anne de Saint Martin; Alexandra Jimenez-Armijo; Elise Schaefer; Gaétan Caravello; Lucas Geyer; Sarah Baer; Laurent Marcoux; François Clauss; Agnès Bloch-Zupan (BMC Oral Health)
Abstract Background The KCNH1 gene (OMIM #603,305) encodes a voltage-gated potassium channel primarily found in the central nervous system. Recent discoveries have linked pathogenic variations in this gene to Temple-Baraitser syndrome (TMBTS, OMIM #611,816) and Zimmermann-Laband syndrome (ZLS, OMIM #135,500). A common manifestation of these syndromes is gingival fibromatosis, which may partially or completely cover tooth crowns, leading in some cases to functional and aesthetic problems, as well as delayed tooth eruption. Case presentation A four-year-old boy and his parents first consulted for delayed primary molars eruption. Shortly after birth, he was diagnosed with a developmental encephalopathy caused by a de novo pathogenic variant in KCNH1. Treatment The first step of oral treatment consisted of myofunctional and speech/language therapy to stimulate biting and chewing. It also helped with the rehabilitation of proper tongue function. This was followed by a gingivoplasty to expose the submerged teeth. We propose a clinical approach to optimize disease management. This aims to minimize complications associated with this rare disorder. Conclusion This case illustrates the need for appropriate and early gingivoplasty to prevent teeth impaction and restore dental function. Additionally, it explores potential complications and provides grounds for a comprehensive protocol for managing gingival fibromatosis for patients with KCNH1 variant.